Moisture damage evaluation of aggregate–bitumen bonds with the respect of moisture absorption, tensile strength and failure surface - Zhang, Jizhe; Airey, Gordon D.; Grenfell, James; Apeagyei, Alex K. (Taylor & Francis, 2017)
The moisture-induced deterioration of asphalt mixture is because of the loss of adhesion at the aggregate–bitumen interface and/or the loss of cohesion within the bitumen film. An experimental study was undertaken in this paper to characterise the effects of moisture on the direct tensile strength of aggregate–bitumen bonds. The aim of this paper was to evaluate the moisture sensitivity of aggregate–bitumen bonds in several different aspects, which included moisture absorption, tensile strength and failure surface examination. Moisture absorption and mineralogical compositions of aggregate were measured using gravimetric techniques and a Mineral Liberation Analyser (MLA), respectively, with the results being used to explain the moisture sensitivity of aggregate–bitumen bonds. Aggregate–bitumen bond strength was determined using a self-designed pull-off system with the capability of accurately controlling the bitumen film thickness. The photographs of the failure surface were quantitatively analysed using Image-J software. The results show that the magnitude of the aggregate–bitumen bonding strength in the dry condition is mainly controlled by bitumen. However, the retained tensile strength after moisture conditioning was found to be influenced by the mineralogical composition as well as the moisture diffusion properties of the aggregates. The linear relationship between retained tensile strength and the square root of moisture uptake suggests that the water absorption process controls the degradation of the aggregate–bitumen bond. The results also suggested that the deterioration of aggregate–bitumen bonds is linked to the decrease in cohesive failure percentage.